(untitled) (Research, Society and Development, 2020)
Objective: to identify hemodynamic and/or oximetric changes resulting from three bed bath techniques in cardiac patients admitted to a Surgical Intensive Care Unit. Method: 3 X 3 crossover clinical trial in which three bed bath technologies were applied to the same individual, at three different times. The interventions considered were: traditional bath at 42.5ºC with monitored and constant water temperature; Bath with 1L vial of distilled water heated for 1 minute in the microwave oven at full power without temperature control; Bath with wet wipes heated for 20 seconds in the microwave oven at full power. Sample comprised of 18 patients in the postoperative period of cardiac surgery. The variables heart rate, respiratory rate, blood pressure (systolic, diastolic and mean), axillary temperature and oxygen saturation using pulse oximetry were analyzed. To compare the means, the ANOVA Two-way test of repeated measures with a pre-established significance level of 5% was used. Results: Sample predominantly composed by male, brown and non-smoker individuals, who underwent coronary artery bypass surgery. There was no significant change in the variables studied (p > 0.05), considering the different types of bath at different times (before, during and after the procedure). Conclusion: Bed bath with water at 42.5 ° C, with heated distilled water vial and wet wipes, in post-cardiac surgery patients admitted to the ICU, does not cause any significant changes in the oxy-hemodynamic variables.